2015
DOI: 10.1108/maj-08-2014-1075
|View full text |Cite
|
Sign up to set email alerts
|

Internal auditors’ perceptions of their role in environmental, social and governance assurance and consulting

Abstract: Purpose – The purpose of this paper is to investigate the nature and extent of internal audit functions’ (IAFs) involvement in environmental, social and governance assurance (ESG) and consulting in Australia. To identify emerging priorities, and the profession’s capacity to respond to these, the paper also explores internal audit practitioners’ perceptions of the current and future importance of these issues and the adequacy of their skills and expertise in meeting the challenges associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 43 publications
2
61
0
3
Order By: Relevance
“…The results confirm our expectations regarding the relationship between IAF characteristics and fees paid to support internal audit activities. We find a positive association between IAF consulting activities and co-sourcing fees, which is in line with the shift from assurance to consulting IAF activities (Allegrini et al, 2011;Soh & Martinov-Bennie, 2015) being likely to accelerate the use of cosourcing. Firms reporting consulting-oriented IAFs should, then, tend to increase internal audit employees' expertise if they want to avoid recurring to co-sourcing.…”
Section: Discussion Of the Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The results confirm our expectations regarding the relationship between IAF characteristics and fees paid to support internal audit activities. We find a positive association between IAF consulting activities and co-sourcing fees, which is in line with the shift from assurance to consulting IAF activities (Allegrini et al, 2011;Soh & Martinov-Bennie, 2015) being likely to accelerate the use of cosourcing. Firms reporting consulting-oriented IAFs should, then, tend to increase internal audit employees' expertise if they want to avoid recurring to co-sourcing.…”
Section: Discussion Of the Resultssupporting
confidence: 84%
“…The shift that internal audit functions (IAFs) have experienced from assurance to consulting activities in many firms (Allegrini, D'Onza, Melville, Sarens, & Selim, 2011;Soh & Martinov-Bennie, 2015) has increased the importance of internal audit in firms' organizations (Speklé, van Elten, & Kruis, 2007), as more consulting-oriented IAFs are better able to enhance corporate governance through their relationships with the audit committee, the management, and the external auditors (Gramling, Maletta, Schneider, & Church, 2004;Hazem & Roberts, 2018). To respond to the increasing importance of IAFs in firms' corporate governance, firms can choose to develop the required internal audit skills and abilities inside an organization, or to adopt the strategy of co-sourcing internal audit activities (Selim, Woodward, & Allegrini, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…IA can also support the external auditor who may rely on work already performed by the IA or request direct assistance when doing an audit (e.g., Maletta, 1993;Felix, Gramling & Maletta, 2001). On top of all of these functions, IA can also be viewed as a consultant, challenging management and acting as a catalyst for improvement, using their knowledge of risk and control to enhance business practices (e.g., Arena & Azzone, 2009;Ma'ayan & Carmeli, 2015;Soh & Martinov-Bennie, 2015).…”
mentioning
confidence: 99%
“…After investigating the role of internal auditors with respect to disclosures of greenhouse gas emissions and energy usage, Trotman and Trotman () concluded that the IAF should play a role in this type of reporting because internal auditors view their function as having become part of the external reporting process. Despite the fact that sustainability issues are expected to increase in the coming years (Soh and Martinov‐Bennie, ; Ridley et al, ), few papers advocate that internal audit should provide assurance concerning sustainability. Its issues remain unclearly defined and are considered less important than other governance issues (Soh and Martinov‐Bennie, ; Ridley et al, ).…”
Section: The Multiple Roles Of Internal Auditmentioning
confidence: 99%
“…Despite the fact that sustainability issues are expected to increase in the coming years (Soh and Martinov‐Bennie, ; Ridley et al, ), few papers advocate that internal audit should provide assurance concerning sustainability. Its issues remain unclearly defined and are considered less important than other governance issues (Soh and Martinov‐Bennie, ; Ridley et al, ). Internal auditors are perceived to have far less expertise on environmental issues than on other topics (Soh and Martinov‐Bennie, ).…”
Section: The Multiple Roles Of Internal Auditmentioning
confidence: 99%